Informação científica e tecnológica no Brasil: análise da produção periódica da Ciência da Informação - Vasconcelos, Mayara Cintya do Nascimento (2020)
The periodical literature is a formal channel for scientific communication offering outstanding subsidy on issues that are in evidence in a particular area. Through the journals it is possible to observe an important activity of the scientific community: communication between researchers. The field of Information Science has since its genesis studies aimed at understanding these practices that involve research results. Due to its importance for the development of society, the analyzes that focus on scientific and technological information are also highlighted in Information Science. For the development of this research, the following question was established as a starting point: what perspectives on scientific and technological information are addressed in the Brazilian journals of Information Science? The main objective of the study is to present an overview of scientific and technological information in the 80s, 90s and 2000s. With the specific objectives: To present and describe quantitative data on the evolution of this production; identify themes conveyed in production through content analysis; and indicate the authors and keywords that are most prominent in each decade. The analysis corpus consists of 348 articles from 11 Brazilian journals in the field of Information Science. Therefore, a qualitative and quantitative approach was used combining the techniques of content analysis and analysis of statistical data. A literature review was carried out, describing the relationship between scientific communication, flow of scientific and technological information and metric studies that are strong instruments for evaluating this production. The results show that the themes addressed in the three decades are concentrated in the following categories: - Management of scientific and technological information for the country's development; - Scientific communication and evaluation of scientific production through metric studies; - Informational competence, construction of knowledge and information technology.